Flavonoids as Inhibitors of Human Butyrylcholinesterase Variants - Maja Katalinić; Anita Bosak; Zrinka Kovarik (Food Technology and Biotechnology, 2014)
The inhibition of butyrylcholinesterase (BChE, EC 3.1.1.8) appears to be of interest in treating diseases with symptoms of reduced neurotransmitter levels, such as Alzheimer’s disease. However, BCHE gene polymorphism should not be neglected in research since it could have an effect on the expected outcome. Several well-known cholinergic drugs (e.g. galantamine, huperzine and rivastigmine) originating from plants, or synthesised as derivatives of plant compounds, have shown that herbs could serve as a source of novel target-directed compounds. We focused our research on flavonoids, biologically active polyphenolic compounds found in many plants and plant-derived products, as BChE inhibitors. All of the tested flavonoids: galangin, quercetin, fisetin and luteolin reversibly inhibited usual, atypical, and fluoride-resistant variants of human BChE. The inhibition potency increased in the following order, identically for all three BChE variants: luteolin<fisetin<quercetin<galangin. The determined enzyme-inhibitor dissociation constants (Ki) ranged from 10 to 170 mmol/L. We showed that no significant change in the inhibition potency of selected flavonoids exists in view of BChE polymorphism. Our results suggested that flavonoids could assist the further development of new BChE-targeted drugs for treating symptoms of neurodegenerative diseases and dementia.